Phosphide-induced PtM ordered alloy composite catalyst as well as preparation method and application thereof

The PtM-MxP/C composite catalyst was formed by the phosphide induction method, which solved the problem of insufficient activity and stability of the Pt-based catalyst, significantly improved the performance of fuel cell catalysts, and was suitable for fuel cell field.

CN119259085AActive Publication Date: 2025-01-07HARBIN INST OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411595718.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-07
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing Pt-based catalysts have low cathode oxygen reduction reaction activity, high cost and insufficient stability in proton exchange membrane fuel cells, making it difficult to meet the strict working environment requirements.

Method used

The phosphide induction method is used to form a PtM-MxP/C composite catalyst through impregnation and evaporation and multi-stage high-temperature heat treatment, where M is Co, Fe or Ni, and an ordered alloy is formed through high-temperature phase change induced to enhance metal-support interaction , improve the stability and activity of the catalyst.

Benefits of technology

The activity and stability of the catalyst are significantly improved. The mass activity of PtCo-Co2P/C catalyst is about 3.4 times that of the latest commercial 10% Pt/C. The half-wave potential attenuation is smaller, and the stability is better than that of commercial catalysts. It is suitable for fuel cell field. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259085A_ABST
    Figure CN119259085A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphide-induced PtM ordered alloy composite catalyst as well as a preparation method and application thereof, relates to a composite catalyst as well as a preparation method and application thereof, and solves the technical problems of low catalytic activity and poor stability of the existing Pt-based catalyst. The catalyst is formed by compounding and uniformly loading an ordered PtM alloy and MxP on a carbon carrier, the ordered PtM alloy is obtained by induction of high-temperature phase change of MxP; wherein M is Co, Fe or Ni, and x is equal to 0.5-3. The preparation method comprises the following steps: dipping Pt, P and M precursors on the surface of a carbon carrier, drying by distillation, performing segmented annealing in inert gas, and grinding. The mass activity of the catalyst provided by the invention is 0.384-0.321 mA / [mu] gPt, which is about 3.4 times of that of commercial 10% Pt / C. Wherein the half-wave potential of the PtCo-Co2P / C is only attenuated by 5mV after 30,000 circles of tests, and the mass activity attenuation rate is 13.44%. The invention can be used in fuel cell field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the preparation of PtM (M = Co, Fe, Ni, etc.) ordered alloys and M x The invention relates to a method and application of a P composite catalyst, belonging to the field of new energy materials. Background Art

[0002] As a clean energy source, proton exchange membrane fuel cells (PEMFC) play an increasingly important role in their field. The traditional Pt / C catalyst is still the most widely used, but its slow cathode oxygen reduction reaction (ORR), low intrinsic activity and high cost limit its further application. On the other hand, due to the harsh working environment of the electrocatalyst, the stability of the catalyst is also very high. The activity and stability of the most commonly used commercial 20% Pt / C have not yet reached a satisfactory level.

[0003] At present, alloying Pt with transition metals can significantly improve the intrinsic activity of the catalyst, while reducing the amount of Pt used and thus reducing costs. Among many alloy catalysts, only PtCo alloy has been put into commercial application, which is a mesoporous carbon-supported PtCo alloy catalyst. However, Pt-based alloys have problems such as metal nanoparticle dissolution, which affects their stability. Summary of the invention

[0004] The present invention aims to solve the technical problems of poor catalytic activity and stability of existing Pt-based catalysts, and to provide a phosphide-induced PtM ordered alloy composite catalyst and its preparation method and application. The present invention uses transition metal phosphide as a precursor, adopts impregnation evaporation and multi-stage high-temperature heat treatment to obtain PtM-M x P / C (M = Co, Fe or Ni) composite catalysts improve the stability of alloy catalysts by increasing the degree of alloy order and enhancing the metal-support interaction. The resulting catalyst Pt activity and stability are significantly higher than the latest commercial Pt / C catalysts.

[0005] The phosphide-induced PtM ordered alloy composite catalyst of the present invention is composed of ordered PtM alloy and M x P is uniformly loaded on a carbon support, and the ordered PtM alloy is composed of M x P is induced by high temperature phase transformation; wherein M is Co, Fe or Ni, and x=0.5~3.

[0006] Furthermore, the loading amount of precious metal Pt in the phosphide-induced PtM ordered alloy composite catalyst is 5 to 20 wt.%.

[0007] The preparation method of the phosphide-induced PtM ordered alloy composite catalyst of the present invention is carried out according to the following steps:

[0008] 1. Precursor impregnation and evaporation: The carbon carrier is dispersed in ultrapure water, and then the Pt source, P source, and M source aqueous solutions are added. After stirring and dispersing for 8 to 12 hours, ultrasonic dispersion is performed for 3 to 4 hours, and then the mixture is placed in a water bath and rotary evaporated to obtain a black solid powder.

[0009] 2. Preparation of PtM-M by multi-stage high temperature heat treatment x P / C composite catalyst: The black powder obtained in step 1 is placed in a high-temperature furnace, calcined and annealed in multiple stages under an inert atmosphere, and then cooled and ground to obtain a PtM ordered alloy composite catalyst, which is denoted as PtM-M. x P / C.

[0010] Furthermore, the carbon carrier described in step 1 is ECP600-jD, EC300J, BP-2000 or XC-72.

[0011] Furthermore, the platinum source described in step 1 is an aqueous solution of chloroplatinic acid;

[0012] Furthermore, the M source described in step 1 is cobalt chloride, cobalt nitrate, nickel chloride, nickel nitrate, ferric chloride or ferric nitrate.

[0013] Furthermore, the concentration of M in the M source aqueous solution described in step 1 is 0.025-5 mol / L.

[0014] Furthermore, the phosphorus source described in step 1 is a sodium hypophosphite aqueous solution with a concentration of 0.025 to 5 mol / L;

[0015] Furthermore, the molar ratio of Pt to M in step 1 is 1:(0.25-5), and the molar ratio of phosphorus to M is 1:(0.5-5).

[0016] Furthermore, the water bath evaporation temperature in step 1 is 70°C to 80°C.

[0017] Furthermore, the inert gas described in step 2 is argon.

[0018] Furthermore, the multi-stage calcination conditions described in step 2 are: the first stage annealing temperature is 200-500°C, the heating rate is 5-10°C / min, and the annealing time is 2-4h; the second stage annealing temperature is 400-800°C, the heating rate is 5-10°C / min, and the annealing time is 2-4h.

[0019] The application of the above-mentioned PtM ordered alloy composite catalyst is to use the catalyst in the oxygen reduction reaction (ORR) of a fuel cell.

[0020] The beneficial effects of the present invention compared to the prior art are:

[0021] (1) The present invention can adsorb Pt, P, M (M = Co, Fe, Ni) precursor salts onto a carbon support by an impregnation evaporation method, and then anneal PtM and M by multiple high-temperature annealing steps. x P is uniformly loaded on the carbon carrier to obtain the composite catalyst PtM-M x P / C;

[0022] (2) By controlling the high temperature annealing conditions, multi-stage calcination is performed on the first formed Pt and M x P, and then induced by high temperature M x P undergoes partial phase transformation and decomposition, and Pt forms a PtM intermetallic compound with M by diffusion. x P formed a heterogeneous composite structure; the resulting PtM-M x The P / C catalyst is evenly dispersed on the surface of the carbon support; the obtained PtM intermetallic compound can effectively enhance the activity and stability of the catalyst. x The presence of P not only regulates the adsorption capacity of Pt for reaction intermediates, but also enhances the metal-support interaction (SMSI) between the carbon support and PtM, further improving the activity and stability of the catalyst.

[0023] The mass activity (MA) of the phosphide-induced PtM ordered alloy composite catalyst of the present invention is 0.384-0.321 mA / μg Pt , which is about 3.4 times the latest commercial 10% Pt / C. 2 After 30,000 cycles of testing, the half-wave potential of P / C only decayed by 5mV, and the mass activity decay rate was 13.44%, which showed good stability. It can be used in the field of fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The PtCo-Co prepared in Example 1 2 XRD patterns of P / C and 10% Pt / C prepared in Comparative Example 1;

[0025] Figure 2 The PtCo-Co prepared in Example 1 2 High magnification TEM image of P / C;

[0026] Figure 3 The PtCo-Co prepared in Example 1 2 High magnification TEM image of P / C;

[0027] Figure 4 The PtCo-Co prepared in Example 1 2 ORR polarization diagram of 10% Pt / C prepared by P / C and Comparative Example 1;

[0028] Figure 5The PtCo-Co prepared in Example 1 and Example 2 2 Mass specific activity diagram of P / C and 10% Pt / C prepared in Comparative Example 1, and Comparative Example 2 Comm. 10% Pt / C;

[0029] Figure 6 The PtCo-Co prepared in Example 1 2 ORR polarization diagram of P / C before and after aging. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0031] Example 1: The preparation method of the phosphide-induced PtM ordered alloy composite catalyst of this example is carried out according to the following steps:

[0032] 1. Precursor impregnation and evaporation: 50 mg of carbon carrier EC300J was dispersed in 60 mL of ultrapure water, and 0.59 mL of 0.0489 mol / L chloroplatinic acid aqueous solution, 0.5 mL of 0.1 mol / L cobalt chloride aqueous solution, and 0.25 mL of 0.05 mol / L sodium hypophosphite aqueous solution were added. After stirring and dispersing for 12 hours, ultrasonic dispersion was performed for 3 hours, and then placed in a water bath and rotary evaporated at a temperature of 75 ° C to obtain a black solid powder;

[0033] 2. PtCo-Co 2 Preparation of P / C composite catalyst: The black solid powder obtained in step 1 is placed in a corundum magnetic boat, and then the magnetic boat is placed in a tube furnace, argon gas is introduced to form an inert atmosphere, and the temperature is increased to 400°C at a heating rate of 10°C / min and maintained for 2h for the first stage annealing, and then the temperature is increased to 700°C at a heating rate of 10°C / min and maintained for 2h for the second stage annealing, and then cooled to room temperature, taken out, and ground evenly to obtain a PtM ordered alloy composite catalyst, recorded as PtCo-Co 2 P / C.

[0034] In this example, PtCo-Co was prepared 2 XRD patterns of P / C catalysts Figure 1 As shown, from Figure 1 It can be seen that the diffraction peaks of the obtained catalyst sample are similar to those of PtCo and Co 2 P standard pdf card matches well, indicating that PtCo and Co 2 P coexistence.

[0035] In this example, PtCo-Co was prepared 2TEM of P / C catalysts Figure 2 and 3 As shown, from Figure 2 It can be seen that the obtained catalyst particles are well dispersed on the surface of the carbon support, and no obvious agglomeration phenomenon occurs. Figure 3 It can be seen that the PtCo particle size is about 4nm, which is similar to Co 2 P particles form a heterogeneous structure.

[0036] Comparative Example 1: In this comparative example, no M source or P source is added, and the Pt nanoparticle oxygen reduction catalyst is directly loaded by the impregnation method. The specific preparation steps are as follows:

[0037] 1. Precursor impregnation and evaporation: 50 mg of carbon carrier EC300J was dispersed in 60 mL of ultrapure water, and 0.59 mL of 0.0489 mol / L chloroplatinic acid aqueous solution was added. After stirring and dispersing for 12 hours, ultrasonic dispersion was performed for 3 hours, and then the mixture was placed in a water bath and rotary evaporated at 75 °C to obtain a black solid powder.

[0038] 2. Preparation of catalyst: Place the powder obtained in step 1 in a corundum magnetic boat, then place the magnetic boat in a tubular furnace, introduce argon gas to form an inert atmosphere, heat to 400°C at a heating rate of 10°C / min and maintain for 2h, cool to room temperature, grind evenly, and obtain Pt / C catalyst.

[0039] Test Example 1 prepared PtCo-Co 2 ORR polarization curves of P / C and 10% Pt / C prepared in comparative example 1. The specific test method is: the electrochemical performance of the catalyst is tested by using the RRDE test system and the electrochemical workstation of Shanghai Chenhua Instrument Co., Ltd. The test system is a three-electrode system, with a glassy carbon electrode as the working electrode, a reversible hydrogen electrode (RHE) as the reference electrode, a platinum wire as the auxiliary electrode, and 0.1M HClO 4 The aqueous solution is the electrolyte. The steps for making the thin film electrode are as follows: weigh 2.5 mg of the catalyst, add 1000 μl of dispersion liquid (a mixed liquid of anhydrous ethanol, ultrapure water, and Nafion solution), ultrasonicate for 40 min to obtain a uniformly dispersed catalyst dispersion, take 20 μL and drop it onto an area of ​​0.2472 cm 2 The working electrode was baked on a glassy carbon electrode with a catalyst surface loading of 0.2 mg Pt / cm 2 The ORR polarization curve was tested by linear sweep voltammetry. O was introduced into the electrolyte for 20 min before the test. 2 The rotation speed of the disk electrode was 1600 rpm until saturation. The scanning rate was 10 mV / s and the potential range was 0.05-1.2 V. Figure 4 The PtCo-Co prepared in Example 1 2ORR polarization diagram of 10% Pt / C prepared by P / C and Comparative Example 1; Figure 4 It can be seen that PtCo-Co 2 The half-wave potential of P / C is 0.905 V and the mass activity (MA) is 0.384 mA / μg Pt , significantly higher than 10% Pt / C. The latter has a half-wave potential of 0.872 V and a mass activity (MA) of 0.0839 mA / μg Pt .

[0040] Comparative Example 2: Purchase the latest commercial 10% Pt / C (Comm. 10% Pt / C) from a certain enterprise and use it directly for testing without any treatment. The mass activity (MA) of the Comm. 10% Pt / C is 0.112 mA / μg Pt .

[0041] Test Example 1 prepared PtCo-Co 2 The mass activity of Comm.10% Pt / C of P / C and Comparative Example 2 is as follows: first, the kinetic current of the catalyst at 0.9V is determined according to the oxygen reduction polarization curve, and the current j at 0.9V in the curve is read. A and the limiting diffusion current j L , then the kinetic current needs to be calculated according to the Koutechy-Levich equation (KL equation for short):

[0042] 1 / j A =1 / j K +1 / j L +1 / j f

[0043] where 1 / j f is very small and can be ignored during calculation, so the KL equation can be simplified to:

[0044] 1 / j A =1 / j K +1 / j L

[0045] Where: j A ——The current at 0.9V in the LSV curve (mA)

[0046] j K ——Calculated kinetic current at 0.9V (mA)

[0047] j L ——Limiting diffusion current in the LSV curve, usually the current at 0.4V (mA)

[0048] Then, using the above kinetic current j KThe mass specific activity of the catalyst was calculated based on the mass of Pt on the electrode.

[0049] MA=j K / m Pt

[0050] Where: MA——mass specific activity (mA / μg Pt )

[0051] j K ——Calculated kinetic current at 0.9V (mA)

[0052] m Pt ——Mass of Pt on the glassy carbon electrode (ug)

[0053] Figure 5 The PtCo-Co prepared in Example 1 2 The mass specific activity diagram of P / C and 10% Pt / C prepared in Comparative Example 1 and Comm.10% Pt / C prepared in Comparative Example 2 is shown in FIG. Figure 5 It can be seen that the PtCo-Co prepared in Example 1 2 The oxygen reduction mass activity of P / C is better than that of Comparative Example 1 and Comparative Example 2. 2 The mass activity (MA) of P / C is 0.384 mA / μg Pt , which is about 3.4 times that of the latest commercial 10% Pt / C (Comparative Example 2).

[0054] The PtCo-Co prepared in Example 1 2 The P / C catalyst was subjected to ORR aging test. The specific test method was: an accelerated aging test was used to evaluate the stability of the catalyst. 2 Cyclic voltammetry scanning test was carried out in saturated electrolyte, with scanning potential of 0.6V-0.95V and scanning speed of 0.2V / s. LSV test was carried out before and after accelerated aging test to compare the difference of ORR polarization curve. Figure 6 The PtCo-Co prepared in Example 1 2 ORR polarization diagram of P / C catalyst before and after aging, from Figure 6 It can be seen that after 30,000 cycles of testing, the half-wave potential decayed by only 5 mV, and the mass activity decay rate was 13.44%. 2 P / C catalyst has good stability.

[0055] Comparative Example 3: This comparative example adopts a high temperature annealing, and the preparation method of the catalyst of this comparative example is carried out according to the following steps:

[0056] 1. Preparation of black solid powder: This step is the same as Example 1;

[0057] 2. PtCo-Co 2 Preparation of P / C composite catalyst: Place the black solid powder obtained in step 1 in a corundum magnetic boat, then place the magnetic boat in a tubular furnace, introduce argon gas to form an inert atmosphere, heat to 700°C at a heating rate of 10°C / min and maintain for 2 hours for annealing, cool to room temperature, take out, and grind evenly to obtain the catalyst.

[0058] The catalyst obtained in this comparative example has a half-wave potential of 0.895 V and a MA of 0.263 mA / μg Pt , which is lower than the performance of the two-stage annealing in Example 1, indicating that the staged annealing is more beneficial to the oxygen reduction performance.

[0059] Example 2: The preparation method of the phosphide-induced PtM ordered alloy composite catalyst of this example is carried out according to the following steps:

[0060] 1. Precursor impregnation and evaporation: 50 mg of carbon carrier ECP600-JD was dispersed in 60 mL of ultrapure water, and 0.59 mL of 0.0489 mol / L chloroplatinic acid aqueous solution, 0.5 mL of 0.1 mol / L cobalt chloride aqueous solution, and 0.25 mL of 0.05 mol / L sodium hypophosphite aqueous solution were added. After stirring and dispersing for 12 hours, ultrasonic dispersion was performed for 3 hours, and then placed in a water bath and rotary evaporated at a temperature of 75 ° C to obtain a black solid powder;

[0061] 2. PtCo-Co 2 Preparation of P / C composite catalyst: The black solid powder obtained in step 1 is placed in a corundum magnetic boat, and then the magnetic boat is placed in a tube furnace, argon gas is introduced to form an inert atmosphere, and the temperature is increased to 400°C at a heating rate of 10°C / min and maintained for 2h for the first stage annealing, and then the temperature is increased to 700°C at a heating rate of 10°C / min and maintained for 2h for the second stage annealing, and then cooled to room temperature, taken out, and ground evenly to obtain a PtM ordered alloy composite catalyst, recorded as PtCo-Co 2 P / C.

[0062] The difference between Example 2 and Example 1 is that the carbon carrier is different, and the obtained PtCo-Co 2 The ORR half-wave potential of the P / C catalyst is 0.902 V, and the MA is 0.363 mA / μg Pt .

[0063] Example 3: The preparation method of the phosphide-induced PtM ordered alloy composite catalyst of this example is carried out according to the following steps:

[0064] 1. Precursor impregnation and evaporation: 50 mg of carbon carrier EC300J was dispersed in 60 mL of ultrapure water, and 0.59 mL of 0.0489 mol / L chloroplatinic acid aqueous solution, 0.5 mL of 0.1 mol / L nickel chloride aqueous solution, and 0.25 mL of 0.05 mol / L sodium hypophosphite aqueous solution were added. After stirring and dispersing for 12 hours, ultrasonic dispersion was performed for 3 hours, and then placed in a water bath and rotary evaporated at a temperature of 75 ° C to obtain a black solid powder;

[0065] 2. PtNi-Ni 2 Preparation of P / C composite catalyst: The black solid powder obtained in step 1 is placed in a corundum magnetic boat, and then the magnetic boat is placed in a tubular furnace, argon gas is introduced to form an inert atmosphere, and the temperature is increased to 400°C at a heating rate of 10°C / min and maintained for 2h for the first stage annealing, and then the temperature is increased to 600°C at a heating rate of 10°C / min and maintained for 2h for the second stage annealing, and then cooled to room temperature, taken out, and ground evenly to obtain a PtM ordered alloy composite catalyst, recorded as PtNi-Ni 2 P / C.

[0066] The difference between Example 3 and Example 1 is that the metal is different, and the obtained PtNi-Ni 2 The half-wave potential of the P / C catalyst is 0.899 V, and the MA is 0.321 mA / μg Pt .

[0067] The present invention uses transition metal phosphide as a precursor, adopts impregnation evaporation and multi-stage high temperature annealing to obtain PtM-M x P / C composite catalyst. The introduced Pt source is first decomposed into Pt in the first high-temperature annealing process, and the M source and P source form M at high temperature. x P, by controlling the annealing conditions, the PtM intermetallic compound and M x Composite structure with coexistence of P. M x The presence of P not only regulates the adsorption capacity of Pt for reaction intermediates, has a strong electronic regulation and anchoring effect on PtNPs, but also enhances the metal-support interaction (SMSI) between carbon support and PtM, thus improving the activity and stability of the catalyst.

Claims

1. A phosphide-induced PtM ordered alloy composite catalyst, characterized in that: The catalyst is composed of an ordered PtM alloy and M x P is uniformly loaded on a carbon support, and the ordered PtM alloy is composed of M x P is induced by high temperature phase transformation; wherein M is Co, Fe or Ni, and x=0.5~3.

2. The phosphide-induced PtM ordered alloy composite catalyst according to claim 1, characterized in that: The loading amount of precious metal Pt in the phosphide-induced PtM ordered alloy composite catalyst is 5 to 20 wt.%.

3. A method for preparing a phosphide-induced PtM ordered alloy composite catalyst according to claim 1, characterized in that: The method proceeds as follows:

1. Precursor impregnation and evaporation: The carbon carrier is dispersed in ultrapure water, and then the Pt source, P source, and M source aqueous solutions are added. After stirring and dispersing for 8 to 12 hours, ultrasonic dispersion is performed for 3 to 4 hours, and then the mixture is placed in a water bath and rotary evaporated to obtain a black solid powder.

2. Preparation of PtM-M by multi-stage high temperature heat treatment x P / C composite catalyst: The black powder obtained in step 1 is placed in a high-temperature furnace, calcined and annealed in multiple stages under an inert atmosphere, and then cooled and ground to obtain a PtM ordered alloy composite catalyst, which is denoted as PtM-M. x P / C.

4. The method for preparing a phosphide-induced PtM ordered alloy composite catalyst according to claim 3, characterized in that: The carbon support described in step 1 is ECP600-jD, EC300J, BP-2000 or XC-72.

5. The method for preparing a phosphide-induced PtM ordered alloy composite catalyst according to claim 3 or 4, characterized in that: The platinum source described in step 1 is an aqueous solution of chloroplatinic acid.

6. The method for preparing a phosphide-induced PtM ordered alloy composite catalyst according to claim 3 or 4, characterized in that: The M source described in step 1 is cobalt chloride, cobalt nitrate, nickel chloride, nickel nitrate, ferric chloride or ferric nitrate.

7. The method for preparing a phosphide-induced PtM ordered alloy composite catalyst according to claim 3 or 4, characterized in that: The phosphorus source described in step 1 is an aqueous solution of sodium hypophosphite.

8. The method for preparing a phosphide-induced PtM ordered alloy composite catalyst according to claim 3 or 4, characterized in that: The molar ratio of Pt to M in step 1 is 1:(0.25-5), and the molar ratio of phosphorus to M is 1:(0.5-5).

9. The method for preparing a phosphide-induced PtM ordered alloy composite catalyst according to claim 3 or 4, characterized in that: The multi-stage calcination conditions described in step 2 are: the first stage annealing temperature is 200-500°C, the heating rate is 5-10°C / min, and the annealing time is 2-4h; the second stage annealing temperature is 400-800°C, the heating rate is 5-10°C / min, and the annealing time is 2-4h.

10. The use of a phosphide-induced PtM ordered alloy composite catalyst according to claim 1, characterized in that: The application is to use the phosphide-induced PtM ordered alloy composite catalyst in the oxygen reduction reaction of fuel cells.

Citation Information

Patent Citations

  • Preparation method of carbon-carried non-crystal alloy catalyst

    CN104148097A

  • Carbon black loaded highly-ordered PtNi intermetallic compound, synthesis method and application thereof

    CN113241453A

  • Method for preparing high-dispersion carbon-supported Pt-based ordered alloy catalyst and catalyst

    CN113600209A

  • Pt-based intermetallic ordered alloy, preparation method and application

    CN115172785A

  • Platinum-rhenium alloy catalyst, preparation method and fuel cell

    CN117558927A